Love and [re]Organising: Rediscovering Architectural Agency Through Gathering - Forde, Tessa (Auckland University of Technology, 2025)
This practice oriented research posits that the architecture discipline is formed not only through the research, conception, and design of buildings and other shared environments but is constructed by and depends on gathering: around ideas, people, actions, values, and shared ritual. In this the history of architecture can be understood as a history of gathering. This suggests that architecture’s gathering spaces: its collectives, institutions, clubs, publications, and so on hold significant sway in what is central to the profession and how this manifests in shared environments. The research presents a theory of the ‘Ground’ discovered through practice—a vast conceptual space of interacting ideas, knowledges, and ways of being that determine real and experienced outcomes in the world. Everything is always producing and interacting with the Ground, but gatherings generate connection to the Ground and allow collective curation and agency in its outcomes. The research suggests that a lack of connection to the Ground of architecture in Aotearoa weakens architecture’s agency, and therefore looks to how architects gather, what they gather around, and how the relational nature of these gathering spaces allows opportunity to imagine, create, discover, reinforce, or influence knowledges and practices and therefore strengthen connection to the Ground. More specifically the research reflects on a series of practice oriented explorations of how to design, organise, envision, enact, and sustain current and new modes of gatherings that can allow architects more agency in anticipating and responding to global challenges and opportunities. From this, the research advances a methodology of Ground-making which involves creating gatherings where ideas and ways of being can be explored, a diverse array of practices can interact and exchange, and where other futures can be imagined and actioned. Ground-making encompasses four practice approaches: 'Traversing The Ground' surveys architecture’s field, a review enlivened by being out and with the world in architecture’s gathering spaces, engaging in architecture discourse across a vast array of sources, and going to events and meet-ups; 'School-making' creates experimental learning platforms for knowledge sharing, creative exploration, and testing and performing other realities; 'Trouble-making' develops strategic actions that critically target the legal and structural systems that underpin the creation of the built environment; 'Creating Community' Infrastructures designs and fosters rituals and relational systems that sustain collective gathering; The research thus seeks to theorise and propose tactics and tools for making gatherings that engage and reveal the Ground. It concludes that for the reimagined gathering spaces to garner momentum, a Ground-maker should engage organising principles capable of creating dynamic connection between diverse and otherwise disparate practices, people, and ideologies; foster deep Love for all beings and things material and immaterial; and emphasise a re-organisation of relationships to each other and the world. Finally, a practice of Ground-making that creates the conditions of possibility for gathering can also offer a methodological approach to conventional architecture practice, proposing methods for the design and nurturing of existing or incidental communities in the imagination and realisation of their shared, public spaces.